Hepatitis B e Antigen Induces NKG2A+ Natural Killer Cell Dysfunction via Regulatory T Cell-Derived Interleukin 10 in Chronic Hepatitis B Virus Infection - Ma, Qingqing; Dong, Xiaoyu; Liu, Siyu; Zhong, Tao; Sun, Dandan; Zong, Lu; Zhao, Changcheng; Lu, Qiong; Zhang, Min; Gao, Yufeng; Ye, Ying; Cheng, Jun; et al. (Frontiers in Cell and Developmental Biology, 2020)
Although persistent hepatitis B virus (HBV) infection is associated with natural killer (NK) cell dysfunction, it remains obscure whether HBV viral antigens are responsible for NK cell dysfunction in patients with chronic hepatitis B (CHB) infection. In this study, we found that the percentage of NK cells expressing the inhibitory receptor, NKG2A, was increased in CHB patients, and NKG2A blockade restored NK cell function. Furthermore, in CHB patients, the frequency of NK cells expressing NKG2A positively correlated with the number of regulatory T cells (Tregs) and production of interleukin-10 (IL-10) in these Tregs. Moreover, exposure of peripheral blood mononuclear cells (PBMCs) isolated from healthy controls to sera from CHB patients resulted in increased proportion of NKG2A+ NK cells; IL-10 blockade reduced the frequency of NKG2A+ NK cells while increasing the percentage of IFN-γ+ NK cells. In addition, stimulation of NK cells and Tregs from healthy controls with CHB sera together with anti-IL-10 antibody increased IFN-γ production in the culture supernatant. The frequencies of NKG2A+ NK cells and IL-10+ Tregs, along with serum levels of alanine transferase and HBV DNA, were significantly increased in CHB patients positive for the Hepatitis B e antigen (HBeAg, a marker of viral replication) when compared to HBeAg-negative CHB patients. Importantly, exposure of PBMCs from healthy controls to HBeAg resulted in increased IL-10 production but reduced levels of TNF and IFN-γ, and IL-10 blockade rescued the generation of TNF and IFN-γ in this assay. The reduced production of TNF and IFN-γ was also observed in NK cells and Tregs from healthy controls that were stimulated with HBeAg, while IL-10 blockade increased the secretion of these two cytokines. We conclude that HBeAg induces IL-10 production in Tregs, thereby leading to increased expression of NKG2A on NK cells, which contributes to NK cell dysfunction during CHB infection. These data suggest that HBeAg is associated with NK cell dysfunction in CHB.